Biopharmaceutics classification system: importance and inclusion in biowaiver guidance - Lorena Barbosa Arrunátegui; Neila Márcia Silva-Barcellos; Karime Rezende Bellavinha; Lisiane da Silveira Ev; Jacqueline de Souza (Universidade de São Paulo, 2015)
Pharmacological therapy is essential in many diseases treatment and it is important that the medicine policy is intended to offering safe and effective treatment with affordable price to the population. One way to achieve this is through biowaiver, defined as the replacement of in vivo bioequivalence studies by in vitro studies. For biowaiver of new immediate release solid oral dosage forms, data such as intestinal permeability and solubility of the drug are required, as well as the product dissolution. The Biopharmaceutics Classification System (BCS) is a scientific scheme that divides drugs according to their solubility and permeability and has been used by various guides as a criterion for biowaiver. This paper evaluates biowaiver application, addressing the general concepts and parameters used by BCS, making a historical account of its use, the requirements pertaining to the current legislation, the benefits and risks associated with this decision. The results revealed that the use of BCS as a biowaiver criterion greatly expands the therapeutics options, contributing to greater therapy access of the general population with drug efficacy and safety guaranteed associated to low cost.